2014
DOI: 10.1177/0160323x14556819
|View full text |Cite
|
Sign up to set email alerts
|

Explaining County Government Fiscal Transparency in an Age of e-Government

Abstract: This research seeks to explain the fiscal transparency practices of individual U.S. counties by examining the extent of information shared with constituents via county government Web sites. This study evaluates a random sample of 400 U.S. counties, where 19 percent of those represented have populations of 100,000 or more residents, matching the same ratio of counties with populations of 100,000 or more residents nationally. We create a four-level categorical dependent variable measuring fiscal transparency and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…There are 1055 counties in the Midwest region of the United States and 239 of those counties (22.65 percent) had no organizational Web site. This number was similar to that reported in Manoharan (2013b;23.5 percent), but lower than that reported by Harder and Jordan (2013;53.33 percent), and higher than that reported by Bernick et al (2014;9 percent). To control for the a priori effect of having no Web site, the analysis included only the 816 counties that had a Web site.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…There are 1055 counties in the Midwest region of the United States and 239 of those counties (22.65 percent) had no organizational Web site. This number was similar to that reported in Manoharan (2013b;23.5 percent), but lower than that reported by Harder and Jordan (2013;53.33 percent), and higher than that reported by Bernick et al (2014;9 percent). To control for the a priori effect of having no Web site, the analysis included only the 816 counties that had a Web site.…”
Section: Resultssupporting
confidence: 84%
“…The presence of a nonwhite population was found to be a statistically significant predictor of governmental transparency (Bernick et al 2014;Borry 2012;Ho 2002;Huang 2007). Therefore:…”
Section: Demographicmentioning
confidence: 92%
See 2 more Smart Citations
“…In the last decade, with evolving e-governance, transparency studies have relied mostly on information available on the community, district and region websites. On the district level, Bernick et al (2014) showed that such factors as appointed county manager, size of county board, number of full-time employees, requirements to submit an audit report to the federal government, unemployment rate, population age, a share of minority residents, heterogeneity of a territorial unit are important to understand the difference in fiscal information online presentation. Lowatcharin and Menifield (2015) analyzed larger district samples from the US Midwest with regard to a broader range of different factors (geographic, demographic, socioeconomic, and institutional) and found that such factors as district area, population density, percentage of minority population, educational attainment, and the council-manager form of government had a positive effect on Internet-backed fiscal transparency.…”
Section: Literature Reviewmentioning
confidence: 99%